The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1088/1742-6596/301/1/012049
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of electroperforated materials using the quadrat counts method

Abstract: The electroperforation distribution in thin porous materials is investigated using the quadrat counts method (QCM), a classical statistical technique aimed to evaluate the deviation from complete spatial randomness (CSR). Perforations are created by means of electrical discharges generated by needle-like tungsten electrodes. The objective of perforating a thin porous material is to enhance its air permeability, a critical issue in many industrial applications involving paper, plastics, textiles, etc. Using ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…This sort of short range repulsion effect between holes can be quantified in terms of the so called inhibition potential. In a previous work [5], we also call the attention on this interpoint interaction and therein the hole distribution was assessed using the quadrat counts method in combination with the Morishita index. On that occasion, it was demonstrated that conclusions drawn from interpoint analysis can be largely affected by the choice of the quadrat size, which is an undesirable feature from the statistical viewpoint.…”
Section: Introductionmentioning
confidence: 99%
“…This sort of short range repulsion effect between holes can be quantified in terms of the so called inhibition potential. In a previous work [5], we also call the attention on this interpoint interaction and therein the hole distribution was assessed using the quadrat counts method in combination with the Morishita index. On that occasion, it was demonstrated that conclusions drawn from interpoint analysis can be largely affected by the choice of the quadrat size, which is an undesirable feature from the statistical viewpoint.…”
Section: Introductionmentioning
confidence: 99%